Comparison between Scotch tape and gel‐assisted mechanical exfoliation techniques for preparation of 2D transition metal dichalcogenide flakes. (1st December 2017) - Budania, Prachi; Baine, Paul T.; Montgomery, John H.; McNeill, David W.; Neil Mitchell, S.J.; Modreanu, Mircea; Hurley, Paul K.
Abstract : The traditional use of Scotch tape for exfoliating layers of two‐dimensional (2D) transition metal dichalcogenides (TMDs) has been compared with a gel‐assisted mechanical exfoliation technique, using MoS2 as a representative TMD. The gel‐assisted exfoliation process, which makes use of both Scotch tape and a gel film, is superior to the use of Scotch tape alone, as it gives a higher probability of obtaining larger surface area few‐layer flakes. A quantitative analysis has been made between the samples prepared by the two techniques. The total density of flakes transferred onto a sample by Scotch tape alone was much higher than when using the gel film. However, most of the transferred flakes were several microns in thickness with lateral dimensions <10 µm. Therefore, the higher percentage of few‐layer flakes with large lateral dimensions (> 20 µm) transferred using gel film is very advantageous. Since samples prepared using gel film have fewer flakes, the contacting of potential thin flakes on the sample can be done conveniently. Also, unlike Scotch tape, the gel film does not leave adhesive residue on the substrate. Optical microscopy, contrast difference measurements and Raman spectroscopy were used for identification of the few‐layer MoS2 flakes.